Near‐tetraploid cancer cells show chromosome instability triggered by replication stress and exhibit enhanced invasiveness. Issue 7 (8th February 2018) - Wangsa, Darawalee; Quintanilla, Isabel; Torabi, Keyvan; Vila‐Casadesús, Maria; Ercilla, Amaia; Klus, Gregory; Yuce, Zeynep; Galofré, Claudia; Cuatrecasas, Miriam; José Lozano, Juan; Agell, Neus; Cimini, Daniela; et al.
Abstract : A considerable proportion of tumors exhibit aneuploid karyotypes, likely resulting from the progressive loss of chromosomes after whole‐genome duplication. Here, by using isogenic diploid and near‐tetraploid (4N) single‐cell‐derived clones from the same parental cell lines, we aimed at exploring how polyploidization affects cellular functions and how tetraploidy generates chromosome instability. Gene expression profiling in 4N clones revealed a significant enrichment of transcripts involved in cell cycle and DNA replication. Increased levels of replication stress in 4N cells resulted in DNA damage, impaired proliferation caused by a cell cycle delay during S phase, and higher sensitivity to S phase checkpoint inhibitors. In fact, increased levels of replication stress were also observed in nontransformed, proliferative posttetraploid RPE1 cells. Additionally, replication stress promoted higher levels of intercellular genomic heterogeneity and ongoing genomic instability, which could be explained by high rates of mitotic defects, and was alleviated by the supplementation of exogenous nucleosides. Finally, our data found that 4N cancer cells displayed increased migratory and invasive capacity, both in vitro and in primary colorectal tumors, indicating that tetraploidy can promote aggressive cancer cell behavior.—Wangsa, D., Quintanilla, I., Torabi, K., Vila‐Casadesús, M., Ercilla, A., Klus, G., Yuce, Z., Galofré, C., Cuatrecasas, M., Lozano, J. J., Agell, N., Cimini, D., Castells, A., Ried, T., Camps, J. Near‐tetraploid cancer cells show chromosome instability triggered by replication stress and exhibit enhanced invasiveness. FASEB J. 32, 3502–3517 (2018). www.fasebj.org